Equivalence classes of exact module categories over graded tensor categories - Mejía Castaño, Adriana (2020)
We describe equivalence classes of indecomposable exact module categories over a finite graded tensor category. When applied to a pointed fusion category, our results coincide with the ones obtained in [11].